Associations between incident breast cancer and ambient concentrations of nitrogen dioxide from a national land use regression model in the Canadian National Breast Screening Study. (December 2019) - Goldberg, Mark S.; Villeneuve, Paul J.; Crouse, Dan; To, Teresa; Weichenthal, Scott A.; Wall, Claus; Miller, Anthony B.
Highlights: Canadian cohort study of about 89, 000 women with up to 25 years of follow-up. Residential exposure to ambient nitrogen dioxide from a national land use regression model. No associations found for postmenopausal women. Pre-menopausal women: rate ratio of 1.17 for an increase of about 10 ppb increase in NO2 . Abstract: Background: Air pollution has been classified as a human carcinogen based largely on epidemiological studies of lung cancer. Recent research suggests that exposure to ambient air pollution increases the risk of female breast cancer especially in premenopausal women. Methods: Our objective was to determine the association between residential exposure to ambient nitrogen dioxide (NO2 ) and newly diagnosed cases of invasive breast cancer in a cohort of 89, 247 women enrolled in the Canadian National Breast Screening Study between 1980 and 1985. Vital status and incident breast cancers through 2005 were determined through record linkage to the Canadian national mortality and cancer registries. Estimates of exposures to NO2 using participants' addresses at time of entry into the study were derived from a national land use regression model. We classified women as reaching menopause according to information obtained at baseline. In addition, as we had no information from women on their menopausal status during the observation period, we conducted analyses using different cut-points for defining postmenopausal status (i.e., at 50 or at 52 years of age), and hence we had four non-independent cohorts. We computed rate ratios for the incidence of breast cancer and their 95% confidence intervals (CI) separately for premenopausal and postmenopausal women. Our Cox models used attained age as the time axis and the rate ratios were adjusted for several individual-level risk factors, including reproductive history, as well as census-based neighborhood-level characteristics. Results: The median concentration of NO2 was about 15 parts per billion (ppb). After adjusting for personal risk factors and contextual variables, we found no evidence of associations for the incidence of breast cancer in the postmenopausal cohorts. In premenopausal women, the rate ratio for an increase of 9.7 ppb (about the interquartile range) was 1.13 (95%CI: 0.94–1.37) for the 50 years of age cut-off for menopausal status and it was 1.17 (95%CI: 1.00–1.38) for the 52 years of age cut-off. Conclusions: Our findings suggest that exposure to low concentrations of NO2, a marker for traffic-related air pollution, increases the risk of premenopausal breast cancer, but not postmenopausal breast cancer.